Dilema Implementasi Kebijakan Digital : Analisis Kesiapan Kepemimpinan Sekolah Dalam Menghadapi Transformasi Pendidikan - Zema Yuliana Aulan; Winengan Winengan; Hadi Kusuma Ningrat (LPPM Institut Pendidikan Nusantara Global, 2026)
Digital transformation in education requires school leadership that is able to translate national digital policies into organizational practices and learning improvement. This study aims to analyze the dilemma of digital policy implementation and examine the readiness of school leadership in facing educational transformation at Pondok Pesantren Al Aziziyah Gunungsari, West Lombok. The research used a qualitative approach with a descriptive-analytical design. Data were collected from eight key informants consisting of the principal, vice principal, teachers, and administrative staff through semi-structured interviews, observation, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldana, including data reduction, data display, and conclusion drawing. The findings indicate that digital transformation is constrained by four interrelated factors: limited digital leadership competence, uneven organizational culture, inadequate technological infrastructure, and the absence of systematic change-management planning. Digital policy implementation is still more dominant in administrative functions than in pedagogical innovation and learning quality improvement. This study emphasizes that school leadership readiness is a decisive factor in ensuring that digitalization becomes a sustainable institutional transformation rather than merely the adoption of digital platforms.